Dependence on prescription medication. Issue 4 (April 2022) - Lucas, Jonathan
In recent years there has been a growing concern among patients and clinicians about dependence on prescription medication. Reports of an 'opioid epidemic' in the United States have sparked fears of a similar problem arising in the UK. This article will explore how clinicians can assess and manage the risks of medication with potential for abuse.